2022
DOI: 10.1039/d2ra01679f
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-PLGA based nanocapsule for the fluorescence spectroscopic detection of dopamine

Abstract: The main purpose of this paper is to design curcumin loaded PLGA nanocapsules for the selective detection of dopamine using fluorescence spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Additionally, some herbal compounds have shown dopaminergic properties; for example, Hepad S1, a Korean medicinal herbal combination, is an important source of dopamine with neuroprotective properties that improve Parkinson’s symptoms; it could modulate adverse cellular events such as inflammation and oxidation in neuronal cells [ 15 ]. Curcumine has shown neuroprotective properties and is an important component of dopamine [ 16 ], and Hordenine, a natural compound of germinated barley, is an agonist of the dopamine D2 receptor [ 17 ]. These and other herbs have been mainly studied in neuronal diseases, with less research in nonneuronal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some herbal compounds have shown dopaminergic properties; for example, Hepad S1, a Korean medicinal herbal combination, is an important source of dopamine with neuroprotective properties that improve Parkinson’s symptoms; it could modulate adverse cellular events such as inflammation and oxidation in neuronal cells [ 15 ]. Curcumine has shown neuroprotective properties and is an important component of dopamine [ 16 ], and Hordenine, a natural compound of germinated barley, is an agonist of the dopamine D2 receptor [ 17 ]. These and other herbs have been mainly studied in neuronal diseases, with less research in nonneuronal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a shift in the emission wavelength and a further change in fluorescence. Similarly, a blue shift in the emission wavelength of CUR was found in Tween 80 micellar nanocurcumin prepared by Pinilla-Peñalver et al ( 2020) and Curcumin-PLGA prepared by Zakaria et al (2022). It was observed that the uptake of CUR-LF NPs was stronger than that of free CUR.…”
Section: Cellular Uptakementioning
confidence: 64%
“…10 In view of the coexistence of AC and DA, there is a demand to distinguish their analytical signals when monitoring the biological level of DA. In recent years, there have been many methods used to detect DA and AC, such as high-performance liquid chromatography, 11 fluorescence, 12 spectrophotometry 13 and mass spectrometry. 14 However, these methods often require specialized operations, long analysis times, high costs and complex equipment.…”
Section: Introductionmentioning
confidence: 99%